PERENCANAAN STRATEGIK USAHA MIKRO DAN KECIL MENENGAH DI DESA TELUK BAKAU KABUPATEN BINTAN - Syuzairi Syuzairi; Ezky Tiyasiningsih; Nurul Yusyawiru; Lastri Anggi Fani; Indra Firdiyansyah; Edinur Ilham; Agriend S. Putra (Bajang Institute, 2023)
The purpose of this service is to provide knowledge and skills for MSMEs in Teluk Bakau Village, Bintan Regency in Small and Medium Enterprises Strategic Planning and to find out the response of MSMEs in Teluk Bakau Village, Bintan Regency with knowledge and skills regarding Small and Medium Enterprises Strategic Planning. The activities carried out by the Community service team are related to the strategic planning of Small and Medium Enterprises so that they can help MSMEs to plan strategically in running their business. The activities carried out can help with the problems of Teluk Bakau Village, Bintan Regency which is a village with the potential for the typical Tanjung Pinang food industry but has not been well organized and with the hope of having skills in strategic planning for its business